2020
DOI: 10.3856/vol48-issue3-fulltext-2436
|View full text |Cite
|
Sign up to set email alerts
|

New records and morphometry of the Atlantic sixgill shark Hexanchus vitulus in the Caribbean coast of Guatemala

Abstract: The present study constitutes the first records and morphometry of Hexanchus vitulus on the Caribbean coast of Guatemala. A total of 10 Atlantic six-gill sharks were captured by artisanal fishers during 2015-2019, showing a sex ratio of 2.3:1 (males:females) and a total length that ranges 61-165 cm. Morphometric measurements are provided for future comparisons in other coastal regions. Recorded sharks corresponded mostly to sexually mature individuals, which differs from that reported for different are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Hacohen-Domené et al (2017) documented two female (28 and 37 cm TL) sharpnose sevengill sharks, Heptranchias perlo, captured in 2016. Avalos-Castillo et al (2020) reported 10 (61-165 cm TL) Atlantic bigeye sixgill sharks, H. vitulus, caught between 2015-2019. In the Caribbean Sea, the sharpnose sevengill shark and the Atlantic bigeye sixgill shark have also been recorded in Colombia (Mejía-Falla & Navia 2019), Jamaica (McLaughlin & Morrissey 2004), and Venezuela (Ehemann et al 2019, Tavares 2019, and additionally, the Atlantic bigeye sixgill shark in the Bahamas (Springer & Waller 1969) and Belize (Daly-Engel et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hacohen-Domené et al (2017) documented two female (28 and 37 cm TL) sharpnose sevengill sharks, Heptranchias perlo, captured in 2016. Avalos-Castillo et al (2020) reported 10 (61-165 cm TL) Atlantic bigeye sixgill sharks, H. vitulus, caught between 2015-2019. In the Caribbean Sea, the sharpnose sevengill shark and the Atlantic bigeye sixgill shark have also been recorded in Colombia (Mejía-Falla & Navia 2019), Jamaica (McLaughlin & Morrissey 2004), and Venezuela (Ehemann et al 2019, Tavares 2019, and additionally, the Atlantic bigeye sixgill shark in the Bahamas (Springer & Waller 1969) and Belize (Daly-Engel et al 2019).…”
mentioning
confidence: 99%
“…Castillo et al 2020). The Cayman Trench extends from the Gulf of Honduras, to which the Guatemalan Caribbean coast belongs, to southeast Cuba.…”
mentioning
confidence: 99%